212k views
1 vote
1. x/x+3 + x+2/x+5

2. x+4/x2+5x+6 • x+3/x2−16
3. 2/x2−9 − 3x/x2−5x+6
4. x+4/x2−5x+6 ÷ x2−16/x+3

Show your work

1 Answer

2 votes

Answer:

1. x = √(73)/2 - 9/2 or x = -9/2 - √(73)/2

2. x = (512 2^(1/3) + (18 i √(16303) + 16222)^(2/3))/(6 (9 i √(16303) + 8111)^(1/3)) + 16/3 or x = 16/3 + (256 (-1)^(2/3))/(3 (1/2 (9 i √(16303) + 8111))^(1/3)) - 1/3 ((-1)/2)^(1/3) (9 i √(16303) + 8111)^(1/3) or x = ((-2)^(2/3) (9 i √(16303) + 8111)^(2/3) - 512 (-2)^(1/3))/(6 (9 i √(16303) + 8111)^(1/3)) + 16/3 or x = 1/3 (10 - 3 √(11))^(-1/3) ((-1)^(1/3) (10 - 3 √(11))^(2/3) - (-1)^(2/3)) - 1/3 or x = 1/3 ((-10 - 3 √(11))^(1/3) - (-1)^(1/3) (3 √(11) - 10)^(1/3)) - 1/3 or x = 1/3 (10 - 3 √(11))^(-1/3) (-(10 - 3 √(11))^(2/3) - 1) - 1/3

3. x = 2/5 or x = (i √(3))/2 - 1/2 or x = -(i √(3))/2 - 1/2

4. x = 1/4 + (4 √(54714) + 441)^(1/3)/(4 3^(2/3)) - 61/(4 (12 √(54714) + 1323)^(1/3)) or x = (-(-3)^(1/3) (4 √(54714) + 441)^(2/3) - 61 (-3)^(2/3))/(12 (4 √(54714) + 441)^(1/3)) + 1/4 or x = (61 (-3/(441 + 4 √(54714)))^(1/3) + (-1)^(2/3) (441 + 4 √(54714))^(1/3))/(4 3^(2/3)) + 1/4

Explanation:

Too long! I try to add to the comments!

User Ian Kirkpatrick
by
5.0k points